Citra Perempuan Jawa dalam Novel â€œSindhen Padmiâ€ Karya Tulus Setyadi: Kajian Feminisme - Rosita, Andjelina Putri; Sulanjari, Bambang (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2023)
The purpose of this research is to uncover the theory of feminism contained in the novel "Sindhen Padmi".Â  This research is about the reality of feminism contained in the novel "Sindhen Padmi". One form of reality contained in the novel "Sindhen Padmi" is gender equality in the social sphere. Javanese people have basic principles about the right inner attitude, namely controlled, calm, level-headed, patient, smooth, tolerance, being simple, honest, sumarah, subtle and not pursuing self-interest. Javanese women are often considered inferior in degree than men. His more passive, meek attitude, and so on are often analogous to women being weak creatures. The image of Javanese women is the main female character and efforts to maintain the image of Javanese women on the main female character. The source of this research data is the novel "Sindhen Padmi" by Tulus Setiyadi published by CV. Weed Library in 2018.